Silicon-regulated antioxidant and osmolyte defense and methylglyoxal detoxification functions co-ordinately in attenuating fluoride toxicity and conferring protection to rice seedlings - Singh, Ankur (Plant physiology and biochemistry : PPB, 2020)
Copyright © 2020 Elsevier Masson SAS. All rights reserved.